2014
DOI: 10.1038/ki.2013.547
|View full text |Cite
|
Sign up to set email alerts
|

The three-year incidence of fracture in chronic kidney disease

Abstract: Knowing a person's fracture risk according to their kidney function, gender, and age may influence clinical management and decision-making. Using healthcare databases from Ontario, Canada, we conducted a cohort study of 679,114 adults of 40 years and over (mean age 62 years) stratified at cohort entry by estimated glomerular filtration rate ((eGFR) 60 and over, 45-59, 30-44, 15-29, and under 15 ml/min per 1.73 m 2 ), gender, and age (40-65 and over 65 years). The primary outcome was the 3-year cumulative incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
159
1
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 219 publications
(170 citation statements)
references
References 57 publications
5
159
1
5
Order By: Relevance
“…Numerous studies have demonstrated increased fracture rates in adults with ESRD [8][9][10][11][12][13][14][15][16][17] and CKD. [20][21][22][23][24][25][26][27][28][29][30][31] With 90% of peak skeletal mass accrued by age 18, children with CKD are uniquely vulnerable to its multiple threats to bone health, but the The total n exceeds 67 first fracture events as there were fractures involving multiple sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have demonstrated increased fracture rates in adults with ESRD [8][9][10][11][12][13][14][15][16][17] and CKD. [20][21][22][23][24][25][26][27][28][29][30][31] With 90% of peak skeletal mass accrued by age 18, children with CKD are uniquely vulnerable to its multiple threats to bone health, but the The total n exceeds 67 first fracture events as there were fractures involving multiple sites.…”
Section: Discussionmentioning
confidence: 99%
“…38 Though not statistically significant after adjustment for PTH, the fully adjusted HR of 2.08 associated with a baseline eGFR,60 ml/min per 1.73 m 2 is highly consistent with findings in adults with CKD. In a recent study of .600,000 individuals $40 years of age, 30 the incidence rate ratio for fracture in 40-65-year-old year old men with an eGFR of 30-44 and 15-29 was 1.7 and 2.2, respectively, compared with the reference group with eGFR$60. Similarly, the rate ratio for fracture in 40-65-year-old women was 2.4 for both an eGFR of 30-44 and eGFR of 15-29 versus eGFR$60.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous clinical studies have demonstrated that the severity of CKD is associated with fracture rate (3,4). Dysregulated mineral homeostasis is a typical feature of CKD (3,4). Therefore, improving bone mineralization and microstructure in patients with CKD is necessary to reduce the risk of fracture.…”
Section: Introductionmentioning
confidence: 99%
“…In the progression of CKD, low glomerular filtration rate (GFR) is associated with excessive phosphorus (P) levels, which accelerate osteocyte-derived fibroblast growth factor-23 (FGF-23) and parathyroid hormone (PTH) secretion and adversely affects bone remodeling and resorption, eventually resulting in osteoporotic bone complications (2). Previous clinical studies have demonstrated that the severity of CKD is associated with fracture rate (3,4). Dysregulated mineral homeostasis is a typical feature of CKD (3,4).…”
Section: Introductionmentioning
confidence: 99%